SOSIALISASI MEMBANGUN JIWA DAN RAGA: PENCEGAHAN PERUNDUNGAN DUNIA MAYA DI LINGKUNGAN SEKOLAH - Bahriansyah, Bahriansyah; Mukhtar, Afiah; Makkulawu, Andi; Asmawiyah, Asmawiyah (Arunika: Jurnal Pengabdian Masyarakat, 2023)
Cyberbullying is a serious threat to students in the era of information technology that continues to develop. This socialization activity was developed by involving the active role of schools, teachers and students which focused on understanding the risks of cyberbullying and strengthening students' social skills. Through participatory methods which include presentation of educational material, discussions and questions and answers. The results of this activity showed a significant increase in students' understanding and their willingness to actively participate in preventing cyberbullying. The aim of this outreach activity is to create a safe, inclusive and supportive school environment, and to increase students' knowledge, understanding and awareness regarding online bullying in order to avoid cyberbullying as both perpetrators and victims.